1993
DOI: 10.1093/genetics/133.4.755
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of natural transformation: testing the DNA repair hypothesis in Bacillus subtilis and Haemophilus influenzae.

Abstract: The hypothesis that the primary function of bacterial transformation is DNA repair was tested in the naturally transformable bacteria Bacillus subtilis and Haemophilus influenzae by determining whether competence for transformation is regulated by DNA damage. Accordingly, DNA damage was induced by mitomycin C and by ultraviolet radiation at doses that efficiently induced a known damage-inducible gene fusion, and the ability of the damaged cultures to transform was monitored. Experiments were carried out both u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 23 publications
0
10
0
4
Order By: Relevance
“…Although bacteria do not go through meiosis, they do exchange genetic information via horizontal gene transfer or HGT [43], through different mechanisms: transformation, the incorporation of foreign DNA into the genome; conjugation, the horizontal transfer of plasmids; transduction, the transfer of genes carried by infecting phages; and integrons, which facilitate the exchange of gene-cassettes in bacterial populations [44]. Empirical evidence suggests that natural competence for transformation is upregulated by multiple stressors (reviewed in [45]), including DNA damage ( [46], but see also [47]) and starvation [48,49]. However, it has also been suggested that stressed microbes take up DNA for reasons other than the generation of genetic variation, such as nutrient consumption and DNA repair [43].…”
Section: (C) Bacteria: Condition-dependent Horizontal Gene Transfermentioning
confidence: 99%
“…Although bacteria do not go through meiosis, they do exchange genetic information via horizontal gene transfer or HGT [43], through different mechanisms: transformation, the incorporation of foreign DNA into the genome; conjugation, the horizontal transfer of plasmids; transduction, the transfer of genes carried by infecting phages; and integrons, which facilitate the exchange of gene-cassettes in bacterial populations [44]. Empirical evidence suggests that natural competence for transformation is upregulated by multiple stressors (reviewed in [45]), including DNA damage ( [46], but see also [47]) and starvation [48,49]. However, it has also been suggested that stressed microbes take up DNA for reasons other than the generation of genetic variation, such as nutrient consumption and DNA repair [43].…”
Section: (C) Bacteria: Condition-dependent Horizontal Gene Transfermentioning
confidence: 99%
“…E. coli is arguably the best studied of all organisms [7]. In contrast, the information that is currently available on the biochemistry and physiology of H. influenzae is limited ( [3,[8][9][10][11] and references therein). Thus, a comparison of the E. coli and H. influenzae genomes is expected to be instrumental in deducing the metabolism of a poorly characterized bacterium from that of a well understood one.…”
Section: Introductionmentioning
confidence: 99%
“…Early experimental evidence indicated an immediate benefit of DNA uptake on transformant survival relative to the remainder of the population in B. subtilis [30][31][32]. However, these earlier results were countered in the same species by evidence that genotoxic stress did not induce competence [33], as predicted by the original idea. A more recent extension of this 'DNA repair hypothesis' proposes that transformation is a general stress response [34].…”
Section: (C) Dna Repairmentioning
confidence: 95%